The notion of physicality in vocal training for the performer in South African theatre, with particular reference to the Alexander technique - Cox, Frances Jayne (Rhodes University, Faculty of Humanities, Department of Drama, 1991)
Voice training has been influenced by separatist attitudes which have allowed for classes which train the body to be separate from those which train the voice. This study acknowledges that to train an actor in separate compartments and then expect the completeness of human expression in performance, is to train under false pretences. There is a need to address the imbalance of separatism and this is examined within the context of voice training. An holistic approach to voice training forms the basis of the argument, which focuses on the need to re-educate the notion of physicality in voice training. Chapter one proposes an understanding of the notion of physicality by drawing on the attitudes of selected theatre practitioners towards the physical nature of the theatre encounter. The expressive energies of the actor's body are responsible for the physicalisation of a play; for this reason the movement of voice and speech is not only examined as source movement, but also as the movement of an actor's response and communication. Chapter two examines some practices which led to attitudes of separatism in voice training, and introduces prevalent practices which are attempting to involve the energy of the physical experience. Chapter three proposes that the Alexander technique be used as the foundation for an awareness of individual physicality. Where chapter one examines the theory of this notion, chapter three proposes an experiential understanding of the same. The Alexander technique is a training in effective body use and it's principles are fundamental to an awareness of body use and functioning. It is argued that these principles should underlie a re-education of physicality. The final chapter of the thesis argues for physicality in South African voice training programmes which would complement the physicality of contemporary theatre forms. It is hoped that this study will provide further incentive for the continued review and adjustment of drama training in South Africa.
Keywords: Voice culture; Alexander technique; Drama -- Study and teaching